Competitive destination analysis in Southern European countries - Águas, Paulo (2012)
Purpose – The purpose of this paper is to analyse the competitiveness of the European Union Member States of Southern Europe (France, Greece, Italy, Portugal and Spain) as tourist destinations for European Union Member States of Central and Northern Europe (Austria, Belgium, Denmark, Finland, Germany, The Netherlands, Ireland, Sweden and the UK). Design/methodology/approach – Application of the market share analysis tool, initially developed by Faulkner, using secondary data from Eurostat – statistical office of the European communities. Findings – The results obtained show that France, Greece, Italy, Portugal and Spain present distinct levels of competitiveness for the various generating countries, with changes having occurred in the period between 1999 and 2007. Originality/value – The paper offers refreshment of Faulkner's tool and an insight into tourist flows in Europe as a tool for tourism and hospitality managers.